PENGEMBANGAN BUKU TEKS BERBASIS PjBL UNTUK MENUMBUHKAN KARAKTER BERWAWASAN LUAS ANAK - Putri Yangga Puspita, Berliana; Ari Nugrahanta, Gregorius (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
Broad-minded character is understood as a person’s perspective to view themselves comprehensively, to be responsive, to make decisions, and to behave positively. The low reading interest among children and the prevalence of bullying cases illustrated a lack of broad-minded character. This study aimed to develop a textbook on road civilization based on Project-Based Learning (PjBL) to foster broad-minded character. This research used the Research & Development (R&D) method with the ADDIE model. Ten certified teachers were involved in the needs analysis, five teachers and five experts acted as expert judges and eight children participated as limited trial subjects. The study results showed that (1) the textbook on road civilization based on Project-Based Learning to foster broad-minded character was developed following the ADDIE steps; (2) the quality of the book fell under the